Brainstem anesthesia as a complication of retrobulbar block (a case report) - N.V. Mynka; A.G. Tutunnyk; V.Yu. Mynka; Yu.Yu. Kobelyatskyy (Медицина неотложных состояний)
The aim of this article is to present a clinical case of brainstem anesthesia after retrobulbar block. Local anesthesia is widely used and an effective method in ophthalmic surgery. It’s based on relatively simple technique of nerve blocks and their safety. However, there is a risk of both local and systemic complications after local anesthesia. Brainstem anesthesia is one of life-threatening systemic complications after retrobulbar block. Implementation of preventive measures described in this article can decrease the risk of this severe complication and emergency care in brainstem anesthesia can save patient’s health and life.